Parastenocarididae (Crustacea, Copepoda, Harpacticoida) of India: description of Parastenocaris mahanadi n. sp., and redescription of P. curvispinus Enckell, 1970 from hyporheic habitats. Zootaxa, 1580, 1–26. (ERRATUM) - Reddy, Y. R.; Defaye, D. (Zootaxa, 2007)
ERRATUM